Kaji Eksperimental Perpindahan Kalor Pada Sistem Lemari Penyimpan Darah - Darmawan Darmawan; Hamdani Hamdani; Ahmad Syuhada (Jurnal Teknik Mesin Unsyiah, 2014)
Blood is the fluid found in all living things serve to transmit substances and oxygen needed by body tissues, carrying chemical products of metabolism, as well as the body's defense against viruses or bacteria. If blood will be donated to another person, the blood will be stored in a blood bag and should be used immediately to the recipient blood. If it is not used directly as they are not needed or should be taken to another place, it must be kept comfortable. Because storage temperature greatly affects the quality of the blood and age of stored blood. Blood storage temperature range from 1 oC to 6 oC, for this reason, it is necessary that both the thermal insulation material storage chamber walls of blood to maintain the desired temperature. Insulation materials used with the value of thermal conductivity (k) is low styrofoam. The purpose of this study was to obtain a blood storage closet systems portable lightweight and easily moveable..